The Statistics and Calculus with Python Workshop A comprehensive introduction to mathematics in Python for artificial intelligence applications - Farrell, Peter (Packt Publishing Limited, 2020)
bWith examples and activities that help you achieve real results, applying calculus and statistical methods relevant to advanced data science has never been so easy/bh4Key Features/h4ulliDiscover how most programmers use the main Python libraries when performing statistics with Python/liliUse descriptive statistics and visualizations to answer business and scientific questions/liliSolve complicated calculus problems, such as arc length and solids of revolution using derivatives and integrals/li/ulh4Book Description/h4Are you looking to start developing artificial intelligence applications? Do you need a refresher on key mathematical concepts? Full of engaging practical exercises, The Statistics and Calculus with Python Workshop will show you how to apply your understanding of advanced mathematics in the context of Python.The book begins by giving you a high-level overview of the libraries you'll use while performing statistics with Python.